Review of Madagascaran Agalliini (Hemiptera: Cicadellidae: Megophthalminae) with descriptions of a new genus and six new species - Viraktamath, C. A.; Gonçalves, Ana Clara (Zootaxa, 2013)
Studies on the Agalliini leafhoppers collected from the Terrestrial Arthropods of Madagascar inventory project of the Cal-ifornia Academy of Sciences, resulted in the discovery of one new genus Agallidwipa gen. nov. (type-species: A. biramosa sp. nov.) with three new species, A. biramosa sp. nov., A. bispinosa sp. nov. and A. webbi sp. nov. and three new species of the genus Igerna Kirkaldy, I. delta sp. nov., I. flavocosta sp. nov. and I. malagasica sp. nov. Two new combinations proposed are Agallidwipa pauliana (Evans) comb. nov. (from genus Agalliana Oman) and Igerna neosa (Webb) comb. nov. (from genus Stonasla White), a species previously recorded from Aldabra Islands. A previous record of Igerna bi-maculicollis (Stål) from Madagascar is shown most likely to be a case of misidentification. All the taxa are described and illustrated. Keys to species of Agalliini from Madagascar are included along with notes on the distinction between Agal-liana and Agallidwipa.